SUMBANGSIH KERAJAAN MUSLIM INDONESIA DALAM PENGEMBANGAN PERADILAN ISLAM: ANALISIS HISTORICAL LEGAL APPROACH - Muhammad Siddiq Armia (Law Department, Sharia and Law Faculty., 2017)
Islamic kingdom in Indonesia made significant role in spreading and enforcing Islamic law. Islamic kingdom not only as a kingdom but also plays their significant role in Islamic tribunal process. Each kingdom has their own judge who came from Islamic scholar school. If they have many difficulties in solving problem they will invite other Islamic scholar from other kingdom to give their opinion. The Islamic scholar has habitual in writing books which is used for further Islamic scholar. Shiratul Mustaqim (Pathway), which was written by Nuruddin Arraniry, was one of famous book among Islamic scholar at that time. Kata Kunci: Sejarah Hukum, Kerajaan Muslim Indonesia, Peradilan Islam